Transoral Segmental Resection and Disarticulation of Mandible with Immediate Nonvascularized Reconstruction: A Case Report. Issue 4 (December 2016) - Gupta, Hemant; Singh, Deepak; Gupta, Sumit; Mehra, Hemant; Singh, Jasmeet; Mishra, Ravish
Disarticulation resections are required for treatment of variety of pathologies of the jaws. These resections are mostly carried out through extraoral approach, which bear significant postoperative morbidity. The transoral approach may be used for this purpose in benign pathological cases of the mandible to limit the postoperative morbidity of extraoral approach, as it provides sufficient access not only for resection and disarticulation but also for immediate reconstruction. This article shares our experience with transoral approach for resection and disarticulation in a case of kerato cystic odontogenic tumor and simultaneous reconstruction. Excellent cosmetic and functional results were observed in 6-month follow-up.